Dual antiplatelet therapy in patients with acute coronary syndrome. Results of actual clinical practice - O. L. Barbarash; V. V. Kashtalap (Российский кардиологический журнал, 2018)
The review article presents the state-of-the-art of use of dual antiplatelet therapy (DAPT) in patients with acute coronary syndrome (ACS) based on modern clinical guidelines and in actual clinical practice. The main differences in the frequency of use and duration of DAPT in different countries are discussed. The study included analysis of the characteristics of patients in randomized clinical trials and patients in actual clinical practice who take DATT after undergoing ACS. Literature sources from open databases PubMed, MEDLINE, eLibrary are used.